2013
DOI: 10.1523/jneurosci.0801-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Taste Familiarity Is Inversely Correlated with Arc/Arg3.1 Hemispheric Lateralization

Abstract: Biochemical, electrophysiological, and imaging studies suggest that the anterior part of the insular cortex (IC) serves as primary taste cortex, whereas fMRI studies in human propose that the anterior IC is also involved in processing of general novelty or saliency information. Here, we compared activity regulated cytoskeleton associated protein (Arc)/Arg3.1 protein levels in the rat IC following administration of familiar versus novel tastes. Surprisingly, there was no correlation between novel taste and Arc/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…That is, the combination of orosensation and postingestive consequences may be more efficient at inducing consolidation than orosensation alone, and that consequently, Arc expression decreases more slowly with repeated exposure to saccharin than with repeated exposure to sucrose. This interpretation is consistent with the recent finding that degree of saccharin experience does not impact saccharin-induced Arc protein expression in the gustatory cortex (Inberg et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…That is, the combination of orosensation and postingestive consequences may be more efficient at inducing consolidation than orosensation alone, and that consequently, Arc expression decreases more slowly with repeated exposure to saccharin than with repeated exposure to sucrose. This interpretation is consistent with the recent finding that degree of saccharin experience does not impact saccharin-induced Arc protein expression in the gustatory cortex (Inberg et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…There was a significant decrease in the number of c-Fos and EGR1 positive neurons following CTA ( Fig. 1d-f; c-Fos, control: 128.13 ± 9.46 positive nuclei/0.1mm 2 , N = 6, CTA: 82.21 ± 11.73 positive nuclei/0.1mm 2 , N = 6 rats, p < 0.01; EGR1, control: 175.90 ± 15.65 positive nuclei/0.1mm 2 , N = 6, CTA: 133.03 ± 10.10 positive nuclei/0.1mm 2 , N = 6, p < 0.05), suggesting that taste/malaise association decreased GC neurons activity, consistent with previous reports testing neuronal activity 2,12 and showing changes in markers for plasticity 10,13 .…”
supporting
confidence: 89%
“…prior to training, whereas the TPE effect is stronger following multiple presentations in the days prior to training; see for more discussion)] it is intriguing to think that TPE stimuli could induce plasticity related genes (Inberg et al 2013;Inberg et al 2016) that are similar to those identified in this earlier work, could act in the same way as behavioral tagging.…”
Section: Possible Cellular Mechanismsmentioning
confidence: 69%
“…If so, perhaps inhibition induced immediately after TPE sessions (or a more molecular perturbation of plasticity such as protein synthesis inhibition, e.g. Ferreira et al 2005;Garcia-DeLaTorre et al 2009;Inberg et al 2013;Levitan et al 2016a) or even between taste deliveries would forestall the CTA enhancement observed here. It would be fascinating and valuable to test the time-course of this phenomenon across hours, as has been done in recent work on CTA consolidation (e.g., Levitan et al 2016a).…”
Section: Gc Plays a Specific Role In Mediating The Impact Of Tpe On Cmentioning
confidence: 94%
See 1 more Smart Citation